Pre‐existing phytoplankton biomass concentrations shape coastal plankton response to fire‐generated ash leachate - Nicholas Baetge; Kimberly H. Halsey; Erin J. Hanan; Michael J. Behrenfeld; Allen J. Milligan; Jason R. Graff; Parker Hansen; Craig A. Carlson; Rene M. Boiteau; Eleanor C. Arrington; Jacqueline Comstock; Elisa R. Halewood; et al. (Limnology and Oceanography, 2025)
Climate‐driven warming is projected to intensify wildfires, increasing their frequency and severity globally. Wildfires are an increasingly significant source of atmospheric deposition, delivering nutrients, organic matter, and trace metals to coastal and open ocean waters. These inputs have the potential to fertilize or inhibit microbial growth, yet their ecological impacts remain poorly understood. This study examines how ash leachate, derived from the 2017 Thomas Fire in California and lab‐produced ash from Oregon vegetation, affects coastal plankton communities. Shipboard experiments off the California coast examined how pre‐existing plankton biomass concentrations mediate responses to ash leachates. We found that ash leachate contained dissolved organic matter (DOM) that significantly increased bacterioplankton specific growth rates and DOM remineralization rates but had a negligible effect on bacterioplankton growth efficiency, suggesting low DOM bioavailability. Furthermore, ash‐derived DOM had a higher potential to accumulate in high biomass water, where pre‐existing DOM substrates may better support bacterial metabolism. Ash leachate had a neutral to negative effect on phytoplankton division rates and decreased microzooplankton grazing rates, particularly in low biomass water, leading to increased phytoplankton accumulation. Nanoeukaryotes accumulated in low biomass water, whereas picoeukaryotes and Synechococcus accumulated in high biomass water. Our findings suggest that the influence of ash deposition on DOM cycling, phytoplankton accumulation, and broader marine food web dynamics depends on pre‐existing biomass levels. Understanding these interactions is critical for predicting the biogeochemical consequences of increasing wildfire activity on marine ecosystems.